Highly Resolved Pure‐Shift Spectra on a Compact NMR Spectrometer. Issue 5 (13th February 2019) - Castaing‐Cordier, Thomas; Bouillaud, Dylan; Bowyer, Paul; Gonçalves, Olivier; Giraudeau, Patrick; Farjon, Jonathan
Abstract: Benchtop NMR spectrometers experience a great success for a wide range of applications. However, their performance is highly limited by peak overlaps. Emerging "pure‐shift NMR" (PS NMR) methods have been intensively used at high field to enhance the resolution by homodecoupling strategies. Here, different PS methods have been implemented on a compact NMR spectrometer operating at 43 MHz. Among the PS methods, the recent PSYCHE scheme appears more sensitive than Zangger‐Sterk (ZS) experiments and offers a substantial resolution improvement as compared to 1D 1 H. On the other hand, despite their slightly lower sensitivity, ZS methods are more efficient to reduce broad signals and are more immune to strong couplings. Finally, the classical J‐resolved pulse sequence is more efficient to reduce larger signals for bigger‐sized molecules. The three approaches appear relevant for benchtop NMR and their combination forms an efficient toolbox to analyze a great diversity of samples. Abstract : Best signal diet ? Pure‐Shift methods are implemented for the first time on a compact NMR spectrometer. Results show that the PSYCHE scheme is usually the most sensitive methods and offers a substantial resolution improvement. Despite their slightly lower sensitivity, Zangger‐Sterk methods are more efficient to reduce broad signals and are more immune to strong couplings. The classical J‐resolved pulse sequence is more efficient to reduce larger signals for bigger‐sized molecules.